PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKANHASIL BELAJAR IPA SISWA KELAS IVA SD NEGERI 115 PEKANBARU - Hendrayenni '; Hamizi '; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :Teaching and learning process conducted student-centered teacher, while students just shut up and accept what is. This makes it less active and creative students in the learning process so as to make the results of student learning rendah.Oleh therefore, that the results of student learning was better, the researchers interested in conducting research that aims to improve learning outcomes siswa.Penelitian IPA is applying the learning model inquiry, held in the State IVA SD class 115 Pekanbaru. Results of this study are: Activity teachers, teacher activities undertaken at the first meeting amounted to 64.3%, then 82.1% in the second meeting, the third meeting increased to 89.3%, and then rose again at the fourth meeting of 96.4%. Student activities, student activities undertaken at the first meeting amounted to 62.5%, then 71.4% in the second meeting, the third meeting increased to 79.4%, and then rose again at the fourth meeting of 87.3%. Results of study, Application of Inquiry Learning Model to improve learning outcomes IPA fourth grade students of State ASD 115 Pekanbaru this can be seen from the value of student learning outcomes on average 56.5 preliminary data, UH-I 65.8 and 76.1 of the UH-II. from initial data to the UH-I increased 9.3 (16%) and of the initial data to the UH-II rise again as much as 19.6 (34.6%). Inlearning outcomes inclassical completenessreaches87.5% andin the classicalcan besaid to becomplete.It can be concludedthattheapplication of theinquiry modelcanimprove learning outcomesof fourth gradescienceState IVA SD115Pekanbaru.Keywords: Inquiry LearningModel, ElementaryScience Lesson, Student Results.